2009
DOI: 10.1007/s10596-009-9175-5
|View full text |Cite
|
Sign up to set email alerts
|

A flow-based pattern recognition algorithm for rapid quantification of geologic uncertainty

Abstract: Geologic uncertainties and limited well data often render recovery forecasting a difficult undertaking in typical appraisal and early development settings. Recent advances in geologic modeling algorithms permit automation of the model generation process via macros and geostatistical tools. This allows rapid construction of multiple alternative geologic realizations. Despite the advances in geologic modeling, computation of the reservoir dynamic response via full-physics reservoir simulation remains a computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, other distance norms can be used as measures of dissimilarity, such as Minkowski, Canberra, chord, dominance, or city-block distance (Alpak et al 2010). Kernel-based clustering methods (Filippone et al 2008) overcome this limitation by embedding the data points into a high-dimensional nonlinear domain and defining their similarity by use of a nonlinear kernel distance function (Kim et al 2004).…”
Section: Methods Enhancementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other distance norms can be used as measures of dissimilarity, such as Minkowski, Canberra, chord, dominance, or city-block distance (Alpak et al 2010). Kernel-based clustering methods (Filippone et al 2008) overcome this limitation by embedding the data points into a high-dimensional nonlinear domain and defining their similarity by use of a nonlinear kernel distance function (Kim et al 2004).…”
Section: Methods Enhancementsmentioning
confidence: 99%
“…This is again not an intuitive conclusion, suggesting that low flow rates can be seen as the cause of screenouts. However, in literature (Cleary et al 1993;Aud et al 1994), field case studies have been reported with such premature or near-well screenouts. This could be caused by poor connection between the wellbore and the created fracture because of well completions, near-wellbore tortuosity, and stress or presence of natural fractures (Urbancic and Maxwell 2002).…”
Section: Case Studiesmentioning
confidence: 99%
“…The objective function can be mathematically expressed as (1) where r o denotes the oil revenue per unit volume, r wp is the injection cost per unit volume, and r wi is the water production cost per unit volume. In Eq.…”
Section: Objective Functionmentioning
confidence: 99%
“…The representative realizations are determined using the flow-based pattern recognition technique documented in Alpak et al (2010). The latter takes advantage of rapid streamline simulation and the Kernel k-Means technologies.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…In recent years, several papers have been published showing the benefits of distance-based techniques applied to ensembles of models for uncertainty quantification, model selection and history matching [2,4,15,20,21]. Scheidt and Caers [20] show how a distance which is well correlated to the difference in flow response can be used to perform uncertainty quantification efficiently.…”
Section: Distance-based Modelingmentioning
confidence: 99%